2004
DOI: 10.2337/diabetes.53.7.1743
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Variant of Ionotropic Glutamate Receptor Regulates Somatostatin Secretion From δ-Cells of Islets of Langerhans

Abstract: Many metabolic factors affect the secretion of insulin from ␤-cells and glucagon from ␣-cells of the islets of Langerhans to regulate blood glucose. Somatostatin from ␦-cells, considered a local inhibitor of islet function, reduces insulin and glucagon secretion by activating somatostatin receptors in islet cells. Somatostatin secretion from ␦-cells is increased by high glucose via glucose metabolism in a similar way to insulin secretion from ␤-cells. However, it is unknown how low glucose triggers somatostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…This theory is supported by the recent finding that glucagon together with Lglutamate, an amino-acid which is co-secreted from pancreatic A-cells, can together stimulate pancreatic SST secretion at low glucose (Muroyama et al, 2004). Also an activation of beta-adrenergic system by hypoglycemia may also lead to increased secretion of SST (Kanatsuka et al, 1981;Hermansen 1980).…”
mentioning
confidence: 91%
“…This theory is supported by the recent finding that glucagon together with Lglutamate, an amino-acid which is co-secreted from pancreatic A-cells, can together stimulate pancreatic SST secretion at low glucose (Muroyama et al, 2004). Also an activation of beta-adrenergic system by hypoglycemia may also lead to increased secretion of SST (Kanatsuka et al, 1981;Hermansen 1980).…”
mentioning
confidence: 91%
“…Islet cells express functional glutamate receptors (9 -12) and vesicular glutamate transporters (13), suggesting that glutamate is a crucial intercellular signal mediator. Glutamate is co-secreted with glucagon, and acute stimulation of its receptors modulates the secretion of glucagon, insulin, and somatostatin (8, 14 -19).…”
mentioning
confidence: 99%
“…13,15) a cells also receive L-glutamate signals by way of a metabotropic glutamate receptor, which causes inhibition of glucagon secretion. 16) Thus, the present study suggests the possibility that D-aspartate also participates in the L-glutamate-mediated intercellular-or intracellular signaling network in islets. In fact, our preliminary experiment indicated that D-aspartate inhibits glucagon secretion, supporting this possibility (Iharada and Moriyama, unpublished observation).…”
Section: Resultsmentioning
confidence: 88%
“…In addition, the KCl-dependent secretion Recent increasing evidence shows that excitatory amino acids are involved in the regulation of hormonal secretion in islets. 15) Islets of Langerhans use L-glutamate as a primary intercellular messenger to regulate the secretion of glucagon, followed by regulation of blood glucose [15][16][17] : L-glutamate is stored in glucagon-containing secretory granules in a cells and co-secreted with glucagon upon low glucose stimulation. L-Glutamate is also present in pancreatic polypeptide-containing secretory granules in a subpopulation of F cells.…”
Section: Resultsmentioning
confidence: 99%